2001
DOI: 10.1046/j.0905-6157.2000.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atopic disorders in children with chronic otitis media with effusion

Abstract: We studied 209 children, referred to a multi-disciplinary 'Glue ear/Allergy' clinic at our hospital with a history of chronic or recurrent otitis media with effusion (OME), in order to determine the prevalence of atopic disease in this population. Referrals were made either from within the hospital by Ear, Nose and Throat (ENT) Surgeons and Audiological Physicians (internal), or by General Practitioners (external). Assessment of atopic status was based on medical history, physical examination, nasal smears and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 15 publications
(14 reference statements)
7
71
2
1
Order By: Relevance
“…It remains difficult to interpret epidemiologic data. The enhanced prevalence of allergy in OME patients reported by some authors (2139,2140) may represent a true finding or may reflect a referral bias.…”
Section: Otitis Media With Effusion (Ome)mentioning
confidence: 93%
“…It remains difficult to interpret epidemiologic data. The enhanced prevalence of allergy in OME patients reported by some authors (2139,2140) may represent a true finding or may reflect a referral bias.…”
Section: Otitis Media With Effusion (Ome)mentioning
confidence: 93%
“…In a case series of 93 children aged 2-10 years referred to a sleep laboratory for polysomnography, sleep apnoea-hypopnoea syndrome was strongly associated with the clinical history of nasal obstruction and AR (32). Chronic middle ear effusion and eustachian tube dysfunction, potentially causing hearing impairment, are associated with rhinitis (33)(34)(35). Local production of nonspecific and specific IgE against both environmental allergens and staphylococcal enterotoxin antigens may be involved in ongoing allergic inflammation observed in the adenoidal lymphatic tissue from atopic children (12,36).…”
Section: Secondary To Infectionmentioning
confidence: 99%
“…Numerous epidemiologic studies have identified allergy as a risk factor for otitis media with effusion [OME]. Alles et al [5] reported an 89% prevalence of allergic rhinitis among OME patients which was significantly higher than the reported prevalence of allergic rhinitis in the general population [6,7]. In other study, otologic symptoms were reported in 32.8% of the children with allergic rhinitis.…”
Section: Discussionmentioning
confidence: 44%